Access to Justice for Women Survivors of Violence in Latin America: Concepts, Paths and Outcomes - Stephanie David and Nadine Jubb (My University, 2016)
The struggle to end domestic violence against women has been called the most successful of the Latin American women’s movement. However, research conducted as part of the project 'Access to Justice for Women Survivors of Violence: A Comparative Study of Women’s Police Stations (WPS) in Latin America' reveals that the contributions of the WPS to women’s access to justice are limited and problematic. The research further suggests that this is due to, among other things, the conflicting concepts around access to justice held by women, justice-sector actors – particularly the Women’s Police Stations – and women’s rights defenders.